FORAGE QUALITY OF DECIDUOUS WOODY AND HERBACEOUS SPECIES THROUGHOUT A YEAR IN MEDITERRANEAN SHRUBLANDS OF WESTERN TURKEY - A. O. Parlak; A. Gokkus; B. H. Hakyemez; H. Baytekin (Journal of Animal and Plant Sciences, 2011)
Nutritional stress during dry summer period is considered as a primary factor limiting goat production in the Mediterranean region. In this study, forage quality of two deciduous woody species (gall oak (Quercus infectoria Oliv.) and Christ’s thorn (Paliurus spina-cristi Mill.)) and herbaceous species in a shrubland in the South Marmara was determined to assess their quality and capacity to meet goats needs. Dry matter (DM), ash, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), dry matter digestibility (DMD), metabolic energy (ME), Phosphorus (P) and Calcium (Ca) were determined in the shrubs and herbaceous. Results showed that DM and Ca in the gall oak were distinctly low in April. On the other hand, its CP and P were high in April while DMD and ME were high in May and June. Contents of DM, ash and Ca in the Christ’s thorn showed a decrease in April-May and those of CP, DMD, and ME increased in May. Herbaceous had their lowest DM, NDF, and ADF in April and highest CP, DMD, and ME in March-April. Consequently, when goats’ needs were considered, goats should be fed with supplementary energy feed throughout the year except for spring months, and with CP during autumn months in order to obtain satisfactory productivity.
Keywords: forage quality; Mediterranean basin; Shrublands; gall oak; Christs thor.n